Modeling of light transmittance measurement in a finite layer of whole blood – a collimated transmittance problem in Monte Carlo simulation and diffusion model - Mroczka, Janusz; Szczepanowski, Remigiusz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
The paper presents the modeling of transmittance measurement in a finite layer of whole blood. To describe light propagation in whole blood medium, a Monte Carlo simulation was used. The propagation of light in whole blood medium in the model required the assumption of photon transport approximation in highly scattering media. We have analyzed collimated-diffuse transmittance, which depended on the technique of free path length simulation. The Monte Carlo simulation was compared with the diffusion model designed for a finite incident light beam and available measurement data of whole blood optical density. The research revealed that discrepancy between the models discussed may be attributed to inaccuracy of the diffusion model due to an increase of anisotropic radiance under the thin sample conditions. Moreover, comparison of the Monte Carlo simulation versus measurement data showed that adding off-sets enabled agreement between them for hematocrit up to 60–70%, which is sufficient for many applications in oximetry. In fact, discrepancy in the Monte Carlo simulation, requiring off-sets to fit measurement data, most likely originates from measurement problem, such as divergence of light source or perturbation of light beam.
Optica Applicata, Vol. 35, 2005, nr 2, s. 311-331
Keywords: optyka; multiple light scattering; Monte Carlo simulation; diffusion model; whole blood